2005
DOI: 10.1089/ars.2005.7.515
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Vasodilatation Induced by Nitrite Instillation in Intestinal Lumen: Possible Role of Hemoglobin

Abstract: It has been shown that nitrite can be reduced to nitric oxide (NO) in intestine and a number of other tissues and released into the blood to form nitrosylhemoglobin (NO-Hb), existing in an equilibrium with S-nitrosohemoglobin. The latter has been suggested to be an NO transporter to distant organs. The aim of this study was to define the pathway of nitrite reduction to form NO in intestinal wall and to estimate whether this pathway has an effect on peripheral circulation. We have shown that in rat intestine at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
34
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 34 publications
1
34
0
Order By: Relevance
“…In the experiments with flap perfusion, we have shown that neither infusion of NO-Hb nor infusion of NO-Hb combined with laser irradiation decreases blood pressure or elevates cGMP levels in circulating blood (Figure 3). Stable blood pressure indicates that spontaneous NO liberation from nitrosyl-hemoglobin does not occur in vivo, which is in line with recently published data (21). In contrast to unaltered MAP and cGMP levels, the concentration of NO-Hb complexes in blood decreased in response to laser irradiation.…”
Section: Effect Of No-hb Infusion and Laser Irradiation On Systemic Csupporting
confidence: 90%
“…In the experiments with flap perfusion, we have shown that neither infusion of NO-Hb nor infusion of NO-Hb combined with laser irradiation decreases blood pressure or elevates cGMP levels in circulating blood (Figure 3). Stable blood pressure indicates that spontaneous NO liberation from nitrosyl-hemoglobin does not occur in vivo, which is in line with recently published data (21). In contrast to unaltered MAP and cGMP levels, the concentration of NO-Hb complexes in blood decreased in response to laser irradiation.…”
Section: Effect Of No-hb Infusion and Laser Irradiation On Systemic Csupporting
confidence: 90%
“…1) (10). Additional studies (43,55,92,93,97) have recently been published confirming the potent vasodilating effects of nitrite. Our group and others have now observed vasodilation at near physiological concentations (Ͻ5 M) in mice, rats, sheep, dogs, primates, and humans.…”
Section: Vasoactivity Of Nitrite In Human Circulationmentioning
confidence: 89%
“…3 The potent vasodilating effects of nitrite have been verified in a number of models. 12,14,19,20,39 The degree to which nitrite-induced vasodilation and coronary collaterals contribute to myocardial protection warrants consideration. It would require a very large sample size to determine the extent to which the statistically insignificant increase in microsphere blood flow (60-minute nitrite group) contributes to myocardial protection because the magnitude of effect is very small.…”
Section: Discussionmentioning
confidence: 99%